Description of the larva of Epigomphus crepidus Kennedy, 1936 (Odonata: Gomphidae) - Novelo-Gutiérrez, Rodolfo; Gómez-Anaya, José Antonio; Smith-Gómez, Sergio Alejandro (Zootaxa, 2015)
The larva of Epigomphus crepidus Kennedy is described and figured and compared with other described congeners. It is characterized by 3rd antennomere spindle-shaped, flattened dorso-ventrally, twice longer than its widest part; ventral pad of hypopharynx pentagonal; prementum subrectangular, with lateral margins slightly convex on apical 0.60; ligula very poorly developed, with a ventral row of nine short, truncate teeth on middle, and dorsal rows of short, stout piliform setae. Abdomen lacking dorsal protuberances, lateral spines on S7–9 divergent; sternites 3–8 divided into five plates, sternites 2 and 9 divided into three plates; male epiproct with a pair of dorsal tubercles rounded apically and divergent at basal 0.30. It differs from other species mainly in 3rd antennomere, sides of prementum and serrations on lateral margins of S7–9.